2017
DOI: 10.1186/s12879-017-2538-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudonocardia carboxydivorans in human cerebrospinal fluid: a case report in a patient with traumatic brain injury

Abstract: BackgroundMembers of the genus Pseudonocardia have been widely reported and recovered from several ecosystems, such as soil samples and plant samples. Pseudonocardia bacteria colonize the microbial communities on the integument of fungus gardening ant species. We present the first documented case of Pseudonocardia carboxydivorans isolated in human cerebrospinal fluid (CSF). To the best of our knowledge, this is the first report of an human infection by P. carboxydivorans. Case presentationA patient, who suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Species of the genus Pseudonocardia have also been isolated from clinical samples and implicated in pathology [ 75 ]. P. carboxydivorans has been isolated from cerebrospinal fluid [ 76 ]. It has also been associated, along with species of other genera ( Saccharomonospora and Saccharopolyspora ), to hypersensitivity pneumonitis [ [77] , [78] , [79] , [80] ].…”
Section: Resultsmentioning
confidence: 99%
“…Species of the genus Pseudonocardia have also been isolated from clinical samples and implicated in pathology [ 75 ]. P. carboxydivorans has been isolated from cerebrospinal fluid [ 76 ]. It has also been associated, along with species of other genera ( Saccharomonospora and Saccharopolyspora ), to hypersensitivity pneumonitis [ [77] , [78] , [79] , [80] ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Fardini et al found that after intravenous injection of gingival plaque samples, some species selectively had a higher prevalence in the placenta than in the oral cavity, which indicated that sometimes the translocation was species specific 20 . Among the bacteria discovered in our study, Pseudonocardia carboxydivorans was isolated from human cerebrospinal fluid (CSF) from individuals suffering from meningitis, indicating its relationship with infectious diseases, which should be further studied 21 . Ascending infections should be alerted among women with PROM, which is commonly recognized.…”
Section: Discussionmentioning
confidence: 93%
“…While these bacteria form mutualistic relationships with coconut plants and plants in general, protecting them against pathogens through the production of secondary metabolites and activation of the plant's immune system, it is important to note that they can pose some environmental concerns. If not properly managed, the antimicrobial properties of these metabolites can disrupt natural Pseudonocardia, which was also a defining feature in Kilifi, is an antifungal commensal microorganism, suggesting that its presence may be linked to the presence of fungal organisms responsible for plant diseases (Navarro-Martínez et al, 2017). Burkholderia, on the other hand, has been implicated in yellowing of leguminous plants (Villarreal, 2017), severe seedborne diseases in rice, wilting symptoms in various crops and also an important causal agent of leaf spots in orchid plants known to grow on various palm trees (Korir et al, 2017;Villarreal, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of Agrobacterium into nonsusceptible plant species through horizontal gene transfer could have unintended consequences (De Saeger et al., 2021). Pseudonocardia , which was also a defining feature in Kilifi, is an antifungal commensal microorganism, suggesting that its presence may be linked to the presence of fungal organisms responsible for plant diseases (Navarro‐Martínez et al., 2017). Burkholderia , on the other hand, has been implicated in yellowing of leguminous plants (Villarreal, 2017), severe seedborne diseases in rice, wilting symptoms in various crops and also an important causal agent of leaf spots in orchid plants known to grow on various palm trees (Korir et al., 2017; Villarreal, 2017).…”
Section: Discussionmentioning
confidence: 99%